Comparison of oral health knowledge, attitudes and practices between grade 10 students from public and private schools in Quezon City - Almerido, Raphaelli Carla L.
INTRODUCTION: The researchers aimed to compare the knowledge, attitudes and practices (KAP) of fourth year high school (Grade 10) students from public and private schools in Quezon City. Other factors affecting KAP of students such as socioeconomic factors, oral health education in school, and environmental factors were also included in the study.